Contrasting mechanisms of magma fragmentation during coeval magmatic and hydromagmatic activity: the Hverfjall Fires fissure eruption, Iceland - Liu, EJ; Cashman, KV; Rust, AC; Höskuldsson, A (Springer Science and Business Media LLC, 2017)
Growing evidence for significant magmatic vesiculation prior to magma-water interaction (MWI) has brought into question the use of ‘diagnostic’ features, such as low vesicularities and blocky morphologies, to identify hydromagmatic pyroclasts. We address this question by quantifying co-variations in particle size, shape and texture in both magmatic and hydromagmatic deposits from the Hverfjall Fires fissure eruption, Iceland. Overlapping vesicularity and bubble number density distributions measured in rapidly quenched magmatic and hydromagmatic pyroclasts indicate a shared initial history of bubble nucleation and growth, with substantial vesiculation prior to MWI. Hydromagmatic fragmentation occurred principally by brittle mechanisms, where the length scale and geometry of fracturing was controlled by the bubble population. This suggests that the elevated fragmentation efficiency of hydromagmatic deposits is driven, at least in part, by brittle disintegration of vesicular pyroclasts due to high thermal stress generated during rapid cooling. In this way, the shape and size distributions of hydromagmatic pyroclasts, both critical input parameters for ash dispersion models, are strongly influenced by the dynamics of vesiculation prior to MWI. This result underlines the need to analyse multiple grain-size fractions to characterise the balance between magmatic and hydromagmatic processes. During the Hverfjall Fires eruption, the external water supply was sufficient to maintain MWI throughout the eruption, with no evidence for progressive exhaustion of a water reservoir. We suggest that both the longevity and the spatial distribution of MWI were determined by the pre-existing regional hydrology and represent continuous interaction between a propagating dike and a strong groundwater flow system hosted within permeable basalt lavas.